Respostas

2013-06-15T10:32:01-03:00

claro que pode.

 

a=1

 

b=-5

 

c= 6

 

                     DELTA =  b²    -  4.a.c

                     DELTA = (-5)² -  4.1.6

                     DELTA = 25    -  24

                     DELTA = 1

 

 

APLICANDO:

 

 X = (-B +OU - A RAIZ DE DELTA) /2.A

 X =  (-(-5)  + OU - A RAIZ DE 1) /2

 X = (5 + OU - 1) /2

 

 X1= (5 + 1) /2 = 6/2= 3

 

 X2= (5 - 1) /2 = 4/2 = 2

 

 

 

                                                         S={3;2}

 

2013-06-15T10:33:15-03:00

a) 1

b)-5

c)6

 

Δ = b² - 4*a*c.

Δ =(-5)*(-5) - 4 * 1*6

Δ =25 - 24

Δ = 1

 

-b= ± √∆

            2*a

-(-5) + 1= 2

                2*1

2/2= 3

 

-(-5) - 1= 4

               2*1 + 2  (  3,2)